The role of laryngopharyngeal reflux in the development of nasopharyngeal manifestations of GERD in preschoolers - Boiarska, L.; Hrebeniuk, L.; Ivanova, K. (Journal of Education, Health and Sport, 2022)
Purpose. To study the level of vitamin D and the levels of antimicrobial peptides in the blood of children suffering from gastroesophageal reflux disease with nasopharyngeal symptoms, to find out how they depend on the composition of refluxate in LFR and how they affect microbial colonization in the nasopharynx. Materials and methods. The clinical study was conducted on the basis of the ENT and the Gastroenterology Departments of the Municipal Non-Commercial Enterprise “City Children's Hospital no. 5" of Zaporizhia City Council. By clinical examination and pH monitoring in the esophagus, the following groups of children 3 to 6 years were established: the 1st group of 22 children with gastroesophageal reflux disease with nasopharyngeal signs, the 2nd group of 22 children with gastroesophageal reflux disease without nasopharyngeal signs. Children were assigned to 1st group on the basis of the presence of clinical manifestations that indicated like a high GER. For children with nasopharyngeal manifestations of GERD, there are not only complaints specific to GERD, as well as symptoms that may indicate LFR: cough after eating and morning hoarseness, redness of the larynx and swelling of the vocal cords.The control group (the 3rd group) consisted of 22 children without pathology from the gastrointestinal tract and ENT systems. The children were tested for the levels of 25(ОН)D3, 1,25(ОН)2D, vitamin D binding protein (DBP), αdefensins 1–3 and cathelicidins. Microbial contamination of the mucous membrane of the nasopharyngeal zone was carried out. As far as the distribution differed from normal one (p<0.05), the data are presented as median and inter-quartile ranges Me (Q25; Q75). The results were processed in Microsoft Excelfor Windows 4.0 and Statistica 6.0. Results. Vitamin D deficiency was revealed in all children of the 1st group (with GERD with LFR). Also, the level of 25(OH)D3 was statistically significantly lower than in children with GERD without LFR and in children of the control group. So, in children of the 1st group, the level 25(ОН)D3 was equel to 13.3 (11.6; 14.9) ng / ml, while in the children of 2nd group it was equal to 21.6 (20.3; 22.9) ng / ml at p < 0.0001 and in children of the control group it was equal to 24.6 (22.8; 28.2) ng / ml at p < 0.0001. The study of the level of antimicrobial peptides showed their significant decrease in children with LFR: the level of αdefensins 1–3 was equel to 2535.0 (1950.0; 3120.0) pg / ml and cathelicidins was equel to 17.9 (5.8; 33.3) ng / ml, which showed a significant statistical difference at p <0.01 compared to other groups. It was noted that in children with acidic and mixed LFR, the level of cathelicidins is lower than in children with alkaline reflux. Thus, in most children with LFR, Haemophilus influenza was detected in nasopharyngeal cultures. Haemophilus influenza in the nose was sown only in children with mixed and acid reflux (30.0% and 80.0%, respectively). This is not typical of children with alkaline reflux. Also, more than two microorganisms were found in half of children with mixed and acid reflux, which was also not registered in children with alkaline reflux (p = 0.05). It was determined that in children with nasopharyngeal manifestations of GERD with Haemophilus influenza in the throat and nose at the same time higher parameters of the total number of acid reflux (180.0 (91.0; 310.0)), the number of prolonged acid reflux (8.0 (4.0; 12.0)) and the percentage of acid reflux per day (20.0 (11.0; 37.6)), which is significant at р˂0,05 than in children when the pathogen was detected only in the throat and in children who do not detected this microorganism Thus, the data obtained confirm that pathological manifestations from the ENT organs are a consequence of the LFR due to GERD. Conclusions. Our study indicates the aggressive effect of acid reflux on the nasopharyngeal mucosa in children suffering from gastroesophageal reflux disease with LFR. Thus, the lack of anti-inflammatory action of cathelicidins due to their increased utilization and reduced formation in conditions of vitamin D deficiency, leads to significant colonization by gram-negative flora, which can contribute to severe disease.